Effect of Reduced Ankle Mobility on Jumping Performance in Young Athletes - Godinho, Ismael (2019)
The objective of this study was to analyze the effects of the reduction of ankle mobility on the jumping performance of young soccer athletes, through a validated jump platform valued and test. Twenty-one soccer players (16.19±0.60 years old, 67.26±5.94 kg weight, 173.81±8.15cm height, 11.29±5.37% estimated body fat, and 8.76±2.70 years of soccer practice) were evaluated and tested for vertical jump performance. Goniometry and Knee-to-Wall tests were adopted in order to evaluate movement and a jump platform was used to evaluate performance. The performance in Counter Movement Jump test correlated positively and significantly not only with right dorsiflexion test but also right Knee-to-Wall test (r = 0.576; p = 0.006, r = 0.513, p = 0.17, respectively). Right Knee-to-Wall is correlated with left Knee-to-Wall (r = 0,816 p = 0,001). Based on the presented data the vertical jump is impaired by ankles mobility deficit.